EFFECTIVENESS OF SECURITY THROUGH OBSCURITY METHODS TO AVOID WEB APPLICATION VULNERABILITY SCANNERS - Kurniawan, Azis; Ramli , Kalamullah (Informatika, Universitas Jenderal Soedirman, 2023)
The concept of security through obscurity is not recommended by the National Institute of Standards and Technology (NIST) as a form of system security. Basically this concept hides assets as difficult as possible so that it is not easy for attackers to find them, so that it can be used to avoid vulnerability scanner applications that are widely used by attackers to find out web system weaknesses. This research was conducted by modifying the web application firewall (WAF) and testing using the SQLMap and OWASP Zed Attack Proxy (ZAP) vulnerability scanner applications. The results of the study show that SQLMap takes up to 1238 times longer to complete a scan on a modified web application firewall than without modification, while OWASP ZAP cannot complete a scan on the same treatment. Thus the concept of security through obscurity can be applied to web security to extend vulnerability scanning time.